Mushkilatu Tanfīdhi Manhaji Qismi Ta’līmi al-Lughati al-Arabiyyati Khilāla Taghayyuri Siyāsati al-Tarbiyyati al-Indonesiyyati: Dirasatu al-Hālati fī Jāmi’ati Madura al-Islamiyyati al- Ḥukūmiyyati - Nurul Hadi; M. Abdul Hamid; Imam Asrori (OKARA: Jurnal Bahasa dan Sastra, 2021)
In Indonesia, higher education curriculum policies have undergone many changes, from KBI, KBK, KPT, KPT-KKNI, and now KPT-KKNI-Merdeka Campus. Every change must leave much time-space for understanding, evaluation to the implementation stage. The reality is that many universities cannot adapt quickly. This study aims to determine how the Arabic Teaching Education Program of IAIN Madura breaks down the courses in a curriculum structure and the problems they face in implementing the curriculum, especially in formulating its curriculum structure. This study used a case study approach. The main subject was the curriculum of Arabic Teaching Education Program of IAIN Madura. Data collection methods used were interviews and documentation. The data analysis technique consisted of three activity lines, data reduction, data presentation, and conclusion drawing. The results showed that the curriculum structure of the Arabic Teaching Education Program of IAIN Madura did not meet the curriculum structure standards as guidelines for curriculum formulation made by the government. The problems in formulating the curriculum structure are 1) Lack of understanding of policymakers on government policies. 2) There is no technical guideline for curriculum development along with the deadline for Study Program Accreditation Renewal. 3) Lack of curriculum development funds.